Medical management of primary vesicoureteric reflux: A changing trend: Single institute experience with 45 patients (77 renal units) over 2 years - Murali, G S; Jadhav, Vinay; Babu, Narendra (Indian Journal of Child Health, 2016)
Background: The management of vesicoureteric reflux (VUR) has undergone a radical change from initial ureteric reimplantation to a more conservative approach. Several studies have demonstrated the validity of this concept by evaluating the role of antibiotic prophylaxis. Recent randomized trials have shown no proven benefits of long-term antibiotic prophylaxis. Objective: The objective of this article is to review the outcome of conservative management of VUR with antibiotic prophylaxis over a period of 2-year. Materials and Methods: A prospective observational study for 2 years was performed in children with primary reflux. They were given continuous antibiotic prophylaxis and regularly followed up every 3 months. Relevant investigations were performed at every follow-up including monitoring of growth parameters. Outcome in terms of recurrent urinary tract infection (UTI) episodes, resolution of VUR, need for definitive surgery were analyzed. Results: Out of initial 48 patients enrolled in the study, three patients were lost for follow-up. Out of 45 patients (77 renal units), most of the patients had Grade III and IV reflux. Scarring was seen predominantly in Grade IV reflux (62.5%). At the end of 2 years, no units demonstrated Grade I reflux. Grade II reflux persisted in 16.67%. Grade III reflux persisted in 23.68%, while Grade IV reflux persisted in 62.5%. Most of the fresh UTI episodes occurred in Grade III and IV VUR patients. Fresh renal scars were seen mostly in Grade IV group. One patient underwent ureteric reimplantation due to fresh renal scar and persistent reflux. Conclusions: Conservative management of VUR with antibiotic prophylaxis appears to be a suitable option without adverse outcomes. In the current scenario, surgery has a minor role to play in the treatment of VUR..